Odkrywanie misji Kościoła w dziełach Thomasa Mertona - Wojciech Oleśków (Studia Paradyskie)
According to Merton, the mission of the Church is to spread the Gospel. Christians discover this mission dynamism through their bond with God. They perceive life’s novelty, which manifests itself in transforming the Christians and people under their charge. What God endows them with is the wisdom to understand His word and to pass it further. Spreading the Gospel happens along with encountering other people and staying close to them. The mission means being open to others, willingness to understand their problems and sources of joy. Christians perceive it as answering Jesus’ call. They are devoted to spread the Gospel. They recognize how and in what way to convey it. The mission is based on God. One can see unity between preaching and contemplating. Prayer is the source of preaching and any commitment. In silence Christians discover God, Who is love. They learn to convey it to others. They strive to share love with others that are in need, poverty and difficulty. An example of the mission discovered by Merton is the apostolate of friendship, which becomes supportive for writers and poets fighting for freedom and truth. The correspondence between Merton and Miłosz shows how one can spread the Gospel, at the same time caring about understanding and getting to know another person.